2020
DOI: 10.12933/therya-20-988
|View full text |Cite
|
Sign up to set email alerts
|

The fate of small-mammal carrion is affected by carcass size and visual conspicuousness in a Neotropical rainforest

Abstract: Scavenging of carrion is essential to terrestrial ecosystems and can shape food webs and behavior. The prevalence and importance of scavenging has often been underestimated and overlooked in food web studies. Small-mammal carrion is even less studied and difficult to estimate, especially in the Neotropics. This project explored small-mammal carcass scavenging in a Neotropical, mid-elevation rainforest, and specifically studied the rate of carcass removal by scavengers, how the conspicuousness and weight of car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Because mammalian scavengers rely on olfactory cues (i.e. volatile organic compounds) to detect and locate carcasses (Butler‐Valverde, DeVault, Rhodes, & Beasley, 2022; DeVault & Rhodes, 2002; Romero, 2020; Ruzicka & Conover, 2012), increased gas production and emissions may increase the likelihood of scavengers detecting carcasses from a distance. In fact, the time‐to‐event analysis of the first visitation showed that the instantaneous probability (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Because mammalian scavengers rely on olfactory cues (i.e. volatile organic compounds) to detect and locate carcasses (Butler‐Valverde, DeVault, Rhodes, & Beasley, 2022; DeVault & Rhodes, 2002; Romero, 2020; Ruzicka & Conover, 2012), increased gas production and emissions may increase the likelihood of scavengers detecting carcasses from a distance. In fact, the time‐to‐event analysis of the first visitation showed that the instantaneous probability (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…These proportions are accurate because the sand piles left by dung beetles at the carcass site are unmistakable signatures of the scavenger identity. The behavior of burying small carcasses and leaving this trace (sand pile) has not been described before in the literature, but it was already observed in a Costa Rican rainforest where dung beetles probably removed a large number of mouse carcasses (Romero 2020). In our study area, most carcasses scavenged by dung beetles (20 out of 23 carcasses) were removed in <72 hours, which supports the high rates of carrion removal observed for dung beetles in other Neotropical areas (Amézquita and Favila 2011).…”
Section: Discussionmentioning
confidence: 99%